2017
DOI: 10.1007/s11096-017-0428-4
|View full text |Cite
|
Sign up to set email alerts
|

Transition of stable patients from traditional anticoagulation clinic services to telephonic management

Abstract: Background Outpatient warfarin dosing and monitoring with telephonic anticoagulation management (TAM) could be an effective alternative to other more labor intensive management models. Objectives To evaluate the time in therapeutic range (TTR) and number of extreme INR values (<1.5 or >4.5) of a telephonic system of warfarin management for stable patients who currently utilized traditional anticoagulation management services (AMSs). Method A retrospective, observational cohort with three groups (1) patients tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 10 publications
1
26
0
Order By: Relevance
“…However, a study by Lee et al revealed opposite results [26]. Some studies have reported similar TTR between online anticoagulation management and regular medical care [27][28][29]. This study showed that the rates of subtherapeutic, supratherapeutic, and extreme subtherapeutic INR values were significantly lower in the Alfalfa app group than in the offline warfarin management group.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…However, a study by Lee et al revealed opposite results [26]. Some studies have reported similar TTR between online anticoagulation management and regular medical care [27][28][29]. This study showed that the rates of subtherapeutic, supratherapeutic, and extreme subtherapeutic INR values were significantly lower in the Alfalfa app group than in the offline warfarin management group.…”
Section: Discussionmentioning
confidence: 59%
“…The studies by Xia et al and Cryder et al showed that there were fewer anticoagulation-related hospital admissions in the online anticoagulation group [4,27]. Most studies have reported that there are no differences in the incidence of major bleeding events between the two groups [5,[27][28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Results from studies with multiple intervention or comparator groups were analyzed as separate comparisons. 12,17 All statistical analyses were completed using StatsDirect Version 3.2.8 (StatsDirect Ltd, Merseyside, England).…”
Section: Data Synthesis and Analysismentioning
confidence: 99%
“…Of the 1125 initial citations, 18 full text articles were screened for eligibility, and 11 studies involving 8395 patients were ultimately included in the systematic review (Table 1). 12,13,15,[17][18][19][20][21][22][23][24] One study was a randomized controlled trial, 22 whereas 10 were retrospective observational studies. 12,13,15,[17][18][19][20][21]23,24 All but 1 study 19 were conducted in the United States.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation